Survival of holm oak woodlands in fire prone landscapes in Northeastern Portugal - Azevedo, João (2009)
It has been observed that holm oak (Quercus rotundifo/ia) woodlands survive wildfires in Northeastern Portugal which sell-extinguish in contact with these woodlands. The mechanisms underlying this phenomenon are unknown. As part 01 an effort to understand the role of holm oak woodlands in landscape fire hazard, we have tested the hypothesis that holm oak woodlands are lire resistant and that this is due to fire behavior modification at the shrubland-woodland interface.